The complete classical music guide - Burrows, John, 1939-; Wiffen, Charles; Ainsley, Robert (DK Publishing, 2020)
Explores the history of Western classical music and the lives of nearly three hundred composers throughout the Middle Ages, Renaissance, Baroque, Classical, Romantic, and modern music eras.